Nano-preservation- A revolutionary approach to improve the shelf-life of fruits: A comprehensive review - Vidthyaa, A; Irene, V P; Ashokkumar, G; Sivakumar, U; Sumithra, A (Plant Science Today, 2025)
Fruits and vegetables can lose their freshness after harvesting due to various factors, including physical damage during harvesting, moisture loss, unfavorable weather conditions and microbial infestations by pests, molds and bacteria. Fruits, particularly, are more prone to spoilage and loss than vegetables. Several preservation techniques are used to enhance the postharvest quality and extend the shelf life of produce. A key emerging method is nano-preservation, which involves advanced technologies such as nano-edible coatings, active packaging, innovative packaging, nanocomposites, nanofilms and nano-biosensors. These techniques aim to improve the preservation of fruits and vegetables, ensuring they stay fresh longer. One of the significant benefits of nanotechnology in food preservation is the design of functional packaging materials that offer superior mechanical properties, better gas permeability and lower bioactive component levels. These materials help extend shelf life while having minimal impact on the sensory attributes like taste, texture and colour of the produce. Compared to traditional preservation methods, nano-preservation provides a more controlled environment around the produce, preventing spoilage, reducing waste and maintaining nutritional value. Additionally, these technologies help reduce the use of chemical preservatives. This review focuses on various nano-preservation techniques and their applications, indicating that nanotechnology is revolutionizing food preservation, offering sustainable development.